Investigation of the Effect of Pressureless Microwave Sintering Parameters on the Corrosion Behavior of Pure Iron Biodegradable Scaffolds - Sharma P.; Pathak D.K.; Pandey P.M. (My University, 2025)
The present study focuses on the systematic analysis to assess the effect of pressureless microwave sintering parameters (PMS) on the corrosion rate of biodegradable iron (Fe) scaffolds. The Fe scaffolds were fabricated using a novel PMS process in combination with a polymer-based 3D printing process. The present study is the first attempt for employing systematic parametric analysis to evaluate the CR of microwave sintered Fe scaffolds. The fabrication experiments were planned using the central composite design method and parameters selected for the analysis were sintering temperature, heating rate, and soaking time with corrosion rate as a response. The corrosion rate was evaluated using a static immersion test at 37 °C in simulated body fluid solution. The results revealed that the maximum corrosion rate was obtained at 700 °C and with the further increase in sintering temperature, a reduction in the corrosion rate was obtained. The corrosion rate was found to decrease with the increase in soaking time and the increase in heating rate. The variation in sintered density and the existence of pores were the major reason behind this effect. Furthermore, the most significant parameter affecting corrosion rate was soaking time with a contribution of 27.50%. Moreover, an optimization was done to evaluate optimum PMS parameters for achieving maximum and minimum corrosion rate in Fe scaffolds using a genetic algorithm technique. Optimization results revealed that the maximum and minimum corrosion rate in Fe scaffolds were obtained at sintering temperature:700 °C; heating rate: 5 °C min; soaking time: 15 min and sintering temperature:1050 °C; heating rate: 5 °C/min and soaking time: 70 min, respectively. © 2022, ASM International.